MENINGKATKAN HASIL BELAJAR SISWA PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM (PAI) DI KELAS V SD NEGERI 035 TARAI BANGUN KECAMATAN TAMBANG KABUPATEN KAMPAR DENGAN MENGGUNAKAN METODE TANYA JAWAB TAHUN 2021 - Salmawati (EduTeach : Jurnal Edukasi dan Teknologi Pembelajaran, 2022)
This classroom action research was carried out at SD Negeri 035 Tarai Bangun, Kampar Regency, which is located in Tambang District, Kampar Regency, Riau Province. Based on the results of classroom action research that has been carried out in PAI learning in class V using the question and answer method, it can be concluded that the use of the question and answer method in PAI learning in class V can improve student learning outcomes. This is evidenced from the average value of the formative test results, in PAI subjects in class V obtained a pre-cycle score of 5.18, cycle I 6.45 and cycle II 7.99 there was a significant increase from each cycle. Thus the use of the question and answer method in PAI learning in elementary school can stimulate students to understand and find solutions to problems they encounter during the learning process, find new ideas and ideas in modifying situations that are witnessed directly, foster critical traits expressed in the form of a willingness to ask questions and express opinions and train students' skills in communicating the results of an activity. activities both orally and in writing. In other words, the use of the question and answer method in learning further improves students' understanding abilities, streamlines the achievement of goals, both general and specific goals and improves student learning outcomes.